Genome sequence of Monilinia vaccinii-corymbosi sheds light on mummy berry disease infection of blueberry and mating type. Issue 2 (4th January 2021) - Yow, Ashley G; Zhang, Yucheng; Bansal, Kamaldeep; Eacker, Stephen M; Sullivan, Shawn; Liachko, Ivan; Cubeta, Marc A; Rollins, Jeffrey A; Ashrafi, Hamid
Abstract: Mummy berry disease, caused by the fungal pathogen Monilinia vaccinii-corymbosi ( Mvc ), is one of the most economically important diseases of blueberries in North America. Mvc is capable of inducing two separate blighting stages during its life cycle. Infected fruits are rendered mummified and unmarketable. Genomic data for this pathogen is lacking, but could be useful in understanding the reproductive biology of Mvc and the mechanisms it deploys to facilitate host infection. In this study, PacBio sequencing and Hi-C interaction data were utilized to create a chromosome-scale reference genome for Mvc . The genome comprises nine chromosomes with a total length of 30 Mb, an N50 length of 4.06 Mb, and an average 413X sequence coverage. A total of 9399 gene models were predicted and annotated, and BUSCO analysis revealed that 98% of 1, 438 searched conserved eukaryotic genes were present in the predicted gene set. Potential effectors were identified, and the mating-type ( MAT ) locus was characterized. Biotrophic effectors allow the pathogen to avoid recognition by the host plant and evade or mitigate host defense responses during the early stages of fruit infection. Following locule colonization, necrotizing effectors promote the mummification of host tissues. Potential biotrophic effectors utilized by Mvc include chorismate mutase for reducing host salicylate and necrotrophic effectors include necrosis-inducing proteins and hydrolytic enzymes for macerating host tissue. The MAT locus sequences indicate the potential for homothallism in the reference genome, but a deletion allele of the MAT locus, characterized in a second isolate, indicates heterothallism. Further research is needed to verify the roles of individual effectors in virulence and to determine the role of the MAT locus in outcrossing and population genotypic diversity.